Preparation method of spherical iron phosphate
A two-step process transforms traditional iron phosphate into ball-shaped material with improved electrochemical performance by controlling pH and heating, addressing the challenges of uniformity and purity in existing methods, resulting in enhanced lithium-ion battery performance.
Patent Information
- Application Number
- CN202411884200.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-14
AI Technical Summary
The existing methods for preparing ball-shaped iron phosphate for lithium-ion batteries face challenges in achieving uniform particle distribution and high chemical purity, which affects the overall battery performance, as traditional forms like olive or peanut shapes are difficult to convert into ball shapes.
A method involving a two-step process: first, a reaction to form a non-crystalline iron phosphate slurry with pH adjustment, followed by washing and heating to create a crystalline form, and then high-temperature calcination to produce ball-shaped iron phosphate, optimizing particle growth and morphology.
The method successfully transforms traditional iron phosphate forms into ball-shaped material with high surface area and uniform pore structure, enhancing electrochemical performance, energy density, and cycle stability, while being energy-efficient and cost-effective for large-scale production.
Smart Images

Figure CN119612468A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, in particular to a method for preparing spherical iron phosphate. Background Art
[0002] With the booming development of new energy industry around the world, the optimization and improvement of the performance of lithium-ion batteries, as the core energy storage components in the field of new energy technology, has put forward more stringent requirements for promoting the development of the entire field of materials science. As an indispensable key component of lithium-ion battery positive electrode materials, the physical form, uniformity of particle size distribution and chemical purity of iron phosphate have a profound impact on the overall performance of the battery.
[0003] Among the various forms of iron phosphate, spherical iron phosphate stands out for its unique advantages. It has a high volumetric capacity, which means that it can store more energy in the same volume. At the same time, its packing density is large, which is conducive to improving the energy density of the battery. In addition, spherical iron phosphate also exhibits excellent fluidity and dispersibility, which is crucial for the uniform coating of positive electrode materials and the stability of battery performance. Therefore, spherical iron phosphate has shown broad application prospects and huge market potential in the field of positive electrode materials for lithium-ion batteries.
[0004] However, traditional iron phosphates are mostly in the shape of olive, peanut or honeycomb. It is not easy to convert them into spherical shapes and to prepare spherical iron phosphate. Therefore, a method for preparing spherical iron phosphate is urgently needed. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a method for preparing spherical ferric phosphate, comprising the following steps: S1, one-step reaction: three solutions of iron salt solution, phosphate salt solution and ammonia water flow in parallel at a molar ratio of 1:0.8-1.2:0.8-1.1 to generate amorphous iron phosphate slurry (i.e. yellow material); ammonia water is added to the iron phosphate slurry (yellow material) to adjust the pH to 1.5-2.5; S2, membrane washing: washing and removing impurities from the iron phosphate slurry by means of a ceramic membrane device, wherein the conductivity of the iron phosphate slurry at the washing end point is less than 5000 μs / cm; S3, second step reaction: add water to the washed iron phosphate slurry, adjust the iron concentration to 0.5-1.2 mol / L, add phosphoric acid solution, heat to 90-120°C, and control the insulation time after the material is converted into white material to 30-90 minutes to obtain white slurry (i.e. white material); S4, washing: adding water to wash the white slurry (white material), the conductivity of the washing water is below 5000μs / cm, and taking the filter cake; S5, drying: the filter cake is dried at a high temperature of 100-500°C to generate ferric phosphate dihydrate; S6. Calcination: The crystal water is completely burned out at a high temperature of more than 500°C to generate spherical iron phosphate.
[0006] Moreover, in S1, the iron salt solution is a ferrous sulfate solution, and the concentration of the ferrous sulfate solution is 180-264 g / L.
[0007] Moreover, in S1, the phosphate salt solution is a monoammonium phosphate solution, and the phosphorus concentration in the phosphate salt solution is 36.9-65.1 g / L.
[0008] Moreover, in the S1, NH4 + The concentration is 15-20%.
[0009] Furthermore, after adding the phosphoric acid solution, the molar ratio of phosphoric acid to iron is 0.2-0.8.
[0010] Moreover, the content of phosphoric acid in the phosphoric acid solution is 78%-88%.
[0011] Furthermore, in S3 and S4, the conductivity of pure water is ≤50 μs / cm.
[0012] Compared with the prior art, the present invention has the following beneficial effects: 1. Through the preparation method provided by the present invention, the growth of primary iron phosphate particles is controlled by adjusting pH=1.5-2.5 in the first-step reaction, and the primary particles are finer and more plastic; the second-step reaction provides a good environment for the conversion of the amorphous iron phosphate slurry into a crystalline state by adding phosphoric acid and controlling the iron concentration, and the crystal growth rate is controlled by raising the reaction temperature to 90-120°C in a high-temperature environment to better generate spherical iron phosphate. The insulation time after the material turns white controls the crystal growth time to avoid over-reaction or under-reaction; the traditional olive-shaped, peanut-shaped or honeycomb-shaped iron phosphate is successfully converted into a spherical shape; the spherical iron phosphate is formed by the accumulation of countless fine particles, and has The high specific surface area increases the contact area of the electrode material, which helps to improve the discharge performance and cycle life of the electrode; spherical iron phosphate has a unique pore structure with uniform pore size and distribution, which can optimize the physical and chemical properties of the electrode and improve the energy density and power density of the battery; spherical iron phosphate can participate in the reaction more evenly during the reaction process, reducing the differences in microscopic components caused by different diffusion pathways, helping to improve the reaction kinetics and making the battery perform better; spherical iron phosphate has a high tap density and small gaps between particles, which is conducive to improving the filling density and utilization rate of the material, and can further improve the energy density and cycle stability of the battery.
[0013] 2. The preparation method of the present invention adopts an efficient and energy-saving production process, which reduces energy consumption and wastewater discharge. At the same time, by precisely controlling process parameters, the utilization rate of raw materials is improved, the production cost is reduced, and it is conducive to large-scale industrial production.
[0014] 3. Since the spherical iron phosphate prepared by the present invention has excellent physical and chemical properties, it is suitable for the preparation of various lithium-ion battery positive electrode materials. In addition, the method can also be appropriately adjusted according to actual needs to meet the requirements of different fields for lithium-ion battery performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a SEM image of the finished ferric phosphate obtained in Example 3; Figure 2 This is a SEM image of the finished ferric phosphate obtained in Comparative Example 1; Figure 3 This is a SEM image of the finished ferric phosphate obtained in Comparative Example 2; Figure 4 This is a SEM image of the finished ferric phosphate obtained in Comparative Example 3; Figure 5 This is the SEM image of the finished iron phosphate obtained in Comparative Example 4. DETAILED DESCRIPTION
[0016] Example 1 A method for preparing spherical ferric phosphate comprises the following steps: S1, one-step reaction: three solutions of iron salt solution, phosphate salt solution and ammonia water flow in parallel at a molar ratio of 1:0.8-1.2:0.8-1.1 to generate amorphous iron phosphate slurry; ammonia water is added to the iron phosphate slurry to adjust the pH to 1.5; S2, membrane washing: washing and removing impurities from the iron phosphate slurry by means of a ceramic membrane device, wherein the conductivity of the iron phosphate slurry at the washing end point is less than 5000 μs / cm; S3, two-step reaction: add pure water to the washed iron phosphate slurry, adjust the iron concentration to 0.5 mol / L, add phosphoric acid solution, heat to 90°C, and control the insulation time after the material is converted into white material for 30 minutes to obtain a white slurry; S4, washing: adding pure water to wash the white slurry, the conductivity of the washing water is below 5000μs / cm, and taking the filter cake; S5, drying: the filter cake is dried at a high temperature of 100°C to generate ferric phosphate dihydrate; S6. Calcination: The crystal water is completely burned out at a high temperature of more than 500°C to generate spherical iron phosphate.
[0017] Furthermore, in S1, the iron salt solution is a ferrous sulfate solution, and the concentration of the ferrous sulfate solution is 180-264 g / L.
[0018] Furthermore, in S1, the phosphate salt solution is a monoammonium phosphate solution, and the phosphorus concentration in the phosphate salt solution is 36.9 g / L.
[0019] Furthermore, in the S1, NH4 + The concentration is 15%.
[0020] Furthermore, in S3, after the phosphoric acid solution is added, the molar ratio of phosphoric acid to iron is 0.2.
[0021] Furthermore, in S3, the content of phosphoric acid in the phosphoric acid solution is 78%.
[0022] Furthermore, in S3 and S4, the conductivity of pure water is ≤50 μs / cm.
[0023] Example 2 A method for preparing spherical ferric phosphate comprises the following steps: S1, one-step reaction: fix the three solutions of iron salt solution, phosphate salt solution and ammonia water in Example 1 in a molar ratio of 1:0.8-1.2:0.8-1.1 to flow in parallel to generate amorphous iron phosphate slurry; add ammonia water to the iron phosphate slurry to adjust the pH to 2.5; S2, membrane washing: washing and removing impurities from the iron phosphate slurry by means of a ceramic membrane device, wherein the conductivity of the iron phosphate slurry at the washing end point is less than 5000 μs / cm; S3, two-step reaction: add pure water to the washed iron phosphate slurry, adjust the iron concentration to 1.2 mol / L, add phosphoric acid solution, heat to 120°C, and control the insulation time after the material is converted into white material to 90 minutes to obtain a white slurry; S4, washing: adding pure water to wash the white slurry, the conductivity of the washing water is below 5000μs / cm, and taking the filter cake; S5, drying: the filter cake is dried at a high temperature of 500°C to generate ferric phosphate dihydrate; S6. Calcination: The crystal water is completely burned out at a high temperature of more than 500°C to generate spherical iron phosphate.
[0024] Furthermore, in S1, the iron salt solution is a ferrous sulfate solution, and the concentration of the ferrous sulfate solution is 180-264 g / L.
[0025] Furthermore, in S1, the phosphate salt solution is a monoammonium phosphate solution, and the phosphorus concentration in the phosphate salt solution is 65.1 g / L.
[0026] Furthermore, in the S1, NH4 + The concentration is 20%.
[0027] Furthermore, in S3, after the phosphoric acid solution is added, the molar ratio of phosphoric acid to iron is 0.8.
[0028] Furthermore, in S3, the content of phosphoric acid in the phosphoric acid solution is 88%.
[0029] Furthermore, in S3 and S4, the conductivity of pure water is ≤50 μs / cm.
[0030] Example 3 A method for preparing spherical ferric phosphate comprises the following steps: S1, one-step reaction: fix the three solutions of iron salt solution, phosphate salt solution and ammonia water in Example 1 in a molar ratio of 1:0.8-1.2:0.8-1.1 to flow in parallel to generate amorphous iron phosphate slurry; add ammonia water to the iron phosphate slurry to adjust the pH to 2.0; S2, membrane washing: washing and removing impurities from the iron phosphate slurry by means of a ceramic membrane device, wherein the conductivity of the iron phosphate slurry at the washing end point is less than 5000 μs / cm; S3, second step reaction: add pure water to the washed iron phosphate slurry, adjust the iron concentration to 1.0 mol / L, add phosphoric acid solution, heat to 105°C, and control the insulation time after the material is converted into white material for 60 minutes to obtain a white slurry; S4, washing: adding pure water to wash the white slurry, the conductivity of the washing water is below 5000μs / cm, and taking the filter cake; S5, drying: the filter cake is dried at a high temperature of 300°C to generate ferric phosphate dihydrate; S6. Calcination: The crystal water is completely burned out at a high temperature of more than 500°C to generate spherical iron phosphate.
[0031] Furthermore, in S1, the iron salt solution is a ferrous sulfate solution, and the concentration of the ferrous sulfate solution is 180-264 g / L.
[0032] Furthermore, in S1, the phosphate salt solution is a monoammonium phosphate solution, and the phosphorus concentration in the phosphate salt solution is 36.9-65.1 g / L.
[0033] Furthermore, in the S1, NH4 + The concentration is 18%.
[0034] Furthermore, in S3, after the phosphoric acid solution is added, the molar ratio of phosphoric acid to iron is 0.5.
[0035] Furthermore, in S3, the content of phosphoric acid in the phosphoric acid solution is 83%.
[0036] Furthermore, in S3 and S4, the conductivity of pure water is ≤50 μs / cm.
[0037] Comparative Example 1 The difference between this comparative example and Example 3 is that during the one-step reaction in step S1, ammonia water is added to adjust the pH value to 1.5.
[0038] Comparative Example 2 The difference between this comparative example and Example 3 is that during the one-step reaction in step S1, ammonia water is added to adjust the pH to 3.3.
[0039] Comparative Example 3 The difference between this comparative example and Example 3 is that, during the second-step reaction in step S3, water is added to the washed ferric phosphate slurry to adjust the iron concentration to 0.2 mol / L.
[0040] Comparative Example 4 The difference between this comparative example and Example 3 is that, during the second-step reaction in step S3, water is added to the washed ferric phosphate slurry to adjust the iron concentration to 1.5 mol / L.
[0041] Experimental Section
[0042] Experiment 1 The finished iron phosphates prepared in Example 3 and Comparative Examples 1-4 were observed using an electron microscope. Figure 1-4 As shown in the figure, it can be seen that the finished iron phosphate product prepared under the conditions of Example 3 presents a regular spherical structure; in contrast, the finished products in Comparative Examples 1 and 2 have undergone significant changes in morphology due to the adjustment of pH value during the preparation process, and the finished products in Comparative Examples 3 and 4 have undergone significant changes in morphology due to the adjustment of iron concentration, turning into irregular shapes.
[0043] This observation reveals the important influence of preparation conditions on the morphology of finished iron phosphate products. The growth pattern and final form of iron phosphate crystals can be significantly changed by adjusting the pH value and iron concentration. Spherical iron phosphate has advantages in certain applications due to its regular morphology and good physical properties (such as fluidity, packing density, etc.). The present invention obtains the spherical iron phosphate of the present invention by precisely controlling the preparation conditions, such as pH value and iron concentration.
[0044] Experiment 2 Take the olive-type iron phosphate prepared by the prior art and the spherical iron phosphate prepared by the present invention, take 4 groups respectively, namely group a, group b, group c, and group d, and measure their BET (specific surface area) and Fe / P (iron-phosphorus ratio), respectively. The results are shown in Table 1.
[0045] Table 1 Physical and chemical indicators of iron phosphate
[0046] It can be seen from Table 1 that spherical iron phosphate has a lower specific surface area (BET value) than olive-type iron phosphate. This feature has a positive effect on improving the compaction performance of the material. The improvement in compaction performance means that when preparing electrodes or other related components, spherical iron phosphate can better adapt to the compression process and form a tighter and more stable structure. The advantage of this structure is that it can reduce porosity and increase the overall density of the material, thereby optimizing the performance of batteries or other electrochemical devices.
[0047] The Fe / P ratio of spherical iron phosphate is relatively high. The increase in the Fe / P ratio usually means that the content of iron in the material is closer to the ideal ratio, which helps to improve the electrical properties of the material. In electrochemical applications, iron is one of the active ingredients, and precise control of its content is crucial to ensuring the conductivity, reaction activity and cycle stability of the material. Therefore, a higher Fe / P ratio may enable spherical iron phosphate to have better performance in electrochemical properties.
Claims
1. A method for preparing spherical ferric phosphate, characterized in that: The steps include: S1, one-step reaction: three solutions of iron salt solution, phosphate salt solution and ammonia water flow in parallel at a molar ratio of 1:0.8-1.2:0.8-1.1 to generate amorphous iron phosphate slurry; ammonia water is added to the iron phosphate slurry to adjust the pH to 1.5-2.5; S2, membrane washing: washing and removing impurities from the iron phosphate slurry by means of a ceramic membrane device, wherein the conductivity of the iron phosphate slurry at the washing end point is less than 5000 μs / cm; S3, two-step reaction: add pure water to the washed iron phosphate slurry, adjust the iron concentration to 0.5-1.2 mol / L, add phosphoric acid solution, heat to 90-120°C, and control the insulation time after the material is converted into white material to 30-90 minutes to obtain a white slurry; S4, washing: adding pure water to wash the white slurry, the conductivity of the washing water is below 5000μs / cm, and taking the filter cake; S5, drying: the filter cake is dried at a high temperature of 100-500°C to generate ferric phosphate dihydrate; S6. Calcination: The crystal water is completely burned out at a high temperature of more than 500°C to generate spherical iron phosphate.
2. The method for preparing spherical ferric phosphate according to claim 1, characterized in that: In S1, the iron salt solution is a ferrous sulfate solution, and the concentration of the ferrous sulfate solution is 180-264 g / L.
3. The method for preparing spherical ferric phosphate according to claim 1, characterized in that: In S1, the phosphate salt solution is a monoammonium phosphate solution, and the phosphorus concentration in the phosphate salt solution is 36.9-65.1 g / L.
4. The method for preparing spherical ferric phosphate according to claim 1, characterized in that: In the S1, NH4 + The concentration is 15-20%.
5. The method for preparing spherical ferric phosphate according to claim 1, characterized in that: In S3, after the phosphoric acid solution is added, the molar ratio of phosphoric acid to iron is 0.2-0.
8.
6. The method for preparing spherical ferric phosphate according to claim 5, characterized in that: In the S3, the content of phosphoric acid in the phosphoric acid solution is 78%-88%.
7. The method for preparing spherical ferric phosphate according to claim 7, characterized in that: In S3 and S4, the conductivity of pure water is ≤50 μs / cm.
Citation Information
Cited By
Preparation method for continuously synthesizing nanoscale sphere-like iron phosphate
CN121085234A
Preparation method of high-sphericity iron phosphate
CN121591183A